Aspects of ancient institutions and geography : studies in honor of Richard J.A. Talbert - Brice, Lee L.; Slootjes, Daniëlle; Talbert, Richard J. A., 1947- (Leiden ; Boston : Brill, 1900)
"In Aspects of Ancient Institutions and Geography, colleagues and students honor Richard J.A. Talbert for his numerous contributions and influence on the fields of ancient history, political and social science, as well as cartography and geography. This collection of original and useful examinations is focused around the core theme of Talbert's work--how ancient individuals and groups organized their world, through their institutions and geography. The first half of the book considers institutional history in chapters on such diverse topics as the Roman Senate, Roman provincial politics and administration, healing springs, gladiators, and soldiers. Chapters on the geography of Thucydides and Alexander III, imperial geography, tracking letters and using sundials round out the second half of the book"--Provided by publisher.
Chaps and maps : reflections on a career with institutional and cartographic history / Lee L. Brice and Danielle Slootjes -- Cumulative bibliography of works by Richard Talbert / Tom Elliott -- Plutarchan prosopography : the cursus honorum / Philip A. Stadter -- The Lex iulia de senatu habendo : a view from the 1930s / Jonathan Scott Perry -- Tacitus on trial(s) / Leanne Bablitz -- Curial communique : memory, propaganda, and the Roman Senate house / Sarah E. Bond -- Second chance for valor : restoration of order after mutinies and indiscipline / Lee L. Brice -- Training gladiators : life in the Ludus / Garrett G. Fagan -- Statuenverehrungen als Zeugnis fur den Einfluss Romischer Amtstrager im Leben in einer Provinz / Werner Eck -- Dio Chrysostom as a local politician : a critical reappraisal / Christopher J. Fuhrmann -- Late antique administrative structures : on the meaning of dioceses and their borders in the fourth century AD / Danielle Slootjes -- The geography of Thucydides / Cheryl L. Golden -- An Anatolian itinerary, 334-333 BC / Fred S. Naiden -- Visualizing empire in imperial Rome / Mary T. Boatwright -- The provinces and worldview of Velleius Paterculus / Brian Turner -- Litterae datae blandone : a letter in search of a posting address / Jerzy Linderski -- Using sundials / George W. Houston -- The healing springs of Latium and Etruria / John F. Donahue -- The shaping hand of the environment : three phases of development in classical antiquity / Michael Maas.
Includes bibliographical references and index.
Keywords: Associations, institutions, etc. -- Rome -- History; Social structure -- Rome -- History; Geography -- Rome -- History; Cartography -- Rome -- History; Civilization, Ancient; Geography, Ancient; Rome -- Civilization; Rome -- Politics and government; Rome -- Social conditions